Linguistic Parameters of the #National Identity of Peruvians through the Prism of Toponymy of Peru - Olga S. Chesnokova; Irina A. Martynenko (RUDN Journal of Language Studies, Semiotics and Semantics)
The motivational features of Peruvian place names as units marking the geophysical, historical, migration, and linguistic-cultural features of the Peruvian ethnic community are revealed. The article interprets the material of the toponymic system of Peru to establish the linguistic parameters of the national identity of the Peruvians. Statistical data on the genesis of toponyms in Peru is derived, their percentage is calculated in the light of the national identity of the Peruvians, the features of geonaming, linguistic creativity, and markers of toponymic identity are established. Peru differs from other countries of the South American continent in the small percentage of Spanish place names per se . Meanwhile, the derived most productive lexical and semantic categories of Hispanic toponymic nomenclature, including hagiotoponyms, commemorative, descriptive toponyms, migrant toponyms, etc., allow us to consider the toponymy of Peru as an organic part of Hispanic geolinguistic system. The corresponding reasons are comprehended and the conditions favorable to the emergence of geonominations in the region are characterized. In particular, it is concluded that Peruvian toponymic periphrases enter into a relationship of intervariant homonymy with toponymic periphrases of other Spanish linguistic cultures. Being an integral toponymic construct, the toponymicon of Peru reveals universal toponymic patterns, such as, for example, migrant toponyms or transfer place names that already exist at a far distance from them. And Spanish-Indian hybrid or blended place names, according to the authors’ calculations, constitute the largest layer in the country’s toponymic corpus. The article shows that as a result of the preservation of the autochthonous toponymic heritage, cultural and linguistic synthesis, the toponymic of Peru acquired original properties that form the Peruvian toponymic code and an organic part of the linguistic parameters of the national identity of the Peruvians.